Synthesis, Characterization, and Application of Antibody Functionalized Fluorescent Silica Nanoparticles. (11th February 2013) - Hurley, Matthew T.; Wang, Zifan; Mahle, Amanda; Rabin, Daniel; Liu, Qing; English, Douglas S.; Zachariah, Michael R.; Stein, Daniel; DeShong, Philip
Abstract Fluorescent silica nanoparticles (FSNs) are prepared by incorporating dye into a mesoporous silica nanoparticle (MSN) synthesis procedure. FSNs containing sulforhodamine B, hydrophobically modified sulforhodamine B, and Cascade Blue hydrazide are made. The MSN‐based FSNs do not leach dye under simulated physiological conditions and have strong, stable fluorescence. FSNs prepared with sulforhodamine B are compared to FSNs prepared with hydrophobically modified sulforhodamine B. The data indicate that FSNs prepared with sulforhodamine B are equally as stable but twice as fluorescent as particles made with hydrophobically modified sulforhodamine B. The fluorescence of a FSN prepared with sulforhodamine B is 10 times more intense than the fluorescence of a 4.5 nm core–shell CdSe/ZnS quantum dot. For diagnostic applications, a method to selectively and covalently bind antibodies to the surface of the FSNs is devised. FSNs that are functionalized with antibodies specific for Neisseria gonorrhoeae specifically bind to Neisseria gonorrhoeae in flow cytometry experiments, thus demonstrating the functionality of the attached antibodies and the potential of MSN‐based FSNs to be used in diagnostic applications.